Grenzobjekte und Medienforschung (hg. von Sebastian Gießmann und Nadine Taha) - Leigh Star, Susan (Locating Media/Situierte Medien, 2017)
Susan Leigh Star's (1954-2010) research encompasses aspects of infrastructural and social theory, knowledge ecologies, feminism and theories of marginality. For the first time, this volume introduces the American science and technology sociologist's most important writings in German. Her texts on border objects, marginality, infrastructures and standards are commented upon by academics and scientists in these fields, and analyzed for their relevance to media studies. With commentaries by Geoffrey C. Bowker, Cora Bender, Ulrike Bergermann, Monika Dommann, Christine Hanke, Bernhard Nett, Jörg Potthast, Gabriele Schabacher, Cornelius Schubert, Erhard Schüttpelz and Jörg Strübing.